2021
DOI: 10.1002/anie.202013465
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Woodward–Hoffmann Stereoselectivity Under Vibrational Strong Coupling

Abstract: Vibrational strong coupling (VSC) has recently been shown to change the rate and chemoselectivity of ground‐state chemical reactions via the formation of light–matter hybrid polaritonic states. However, the observation that vibrational‐mode symmetry has a large influence on charge‐transfer reactions under VSC suggests that symmetry considerations could be used to control other types of chemical selectivity through VSC. Here, we show that VSC influences the stereoselectivity of the thermal electrocyclic ring op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 41 publications
0
92
0
Order By: Relevance
“… 38 Another interesting work is to see the breaking of the Woodward–Hoffmann rule and the modification of stereoselectivity under VSC. 39 We have recently shown that cooperative VSC of solute to solvent molecules can drastically modify the chemical reaction rate. 40 A similar approach was also used to control enzyme hydrolysis by coupling to water molecules.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Another interesting work is to see the breaking of the Woodward–Hoffmann rule and the modification of stereoselectivity under VSC. 39 We have recently shown that cooperative VSC of solute to solvent molecules can drastically modify the chemical reaction rate. 40 A similar approach was also used to control enzyme hydrolysis by coupling to water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the case of the strong coupling regime, the photon can mediate hybridization of the electromagnetic field to achieve energy splitting of polaritonic states. ,, As a result, observed Rabi splitting frequency is larger value than sum of photon loss rate and dephasing rate. Recently, polaritonic states have been used to transform ground-state molecular properties via formation of a vacuum strong coupling state. This concept can also be applied to the vibrational states of molecules; placing molecules in a microscale cavity induces the vibro-polaritonic states, which leads to modification of the ground-state thermochemical reactivity via vacuum vibrational coupling. This vacuum vibrational strong coupling is also used to modify Raman scattering, , vibro-polaritonic infrared (IR) emissions, the self-assembly of molecules, , ferromagnetism, and even the superconductivity of materials . Recently, we also investigated the use of vacuum vibrational coupling to modify the proton conductivity of aqueous electrolyte solutions .…”
Section: Introductionmentioning
confidence: 99%
“…In the last several years, it has been shown that coupling vibrational modes in this way has a pronounced effect on chemistry and molecular properties. [3,[5][6][7][8][9][10][11][12][13][14][15][16][17]20] In this vibrational strong coupling regime (VSC), vibro-polaritonic states (VP + , VPÀ) are formed, separated by the so-called Rabi splitting energy (" h W R ) (Figure 1 a). In typical experiments, a large number N of molecules are coupled by VSC to a single optical mode which leads to the formation of N-1 dark states (DS) which are, together with VP + and VPÀ, delocalized over many molecules.…”
mentioning
confidence: 99%